Karya Tari Nan Tingga Merepresentasikan Ketidakterimaan Dan Keikhlasan Terhadap Kematian Dalam Tradisi Ba Ilau - Azzahra Putri; Kurniadi Ilham; Emri Emri; Dony Osmond (INDO PUBLISHING, 2026)
The dance work Nan Tingga is inspired by the social phenomenon of the Ba Ilau tradition. This interest is based on the sadness of a mother over the loss of her child who died abroad, the focus of the problem that became the idea to represent is about the unacceptance and sincerity of death. This work is worked on in two streams of work on the atmosphere with cultural themes and dramatic types, the method that the artist uses is referring to the book written by Prof. Dr. Y. Sumandiyo Hadi, namely the book on the basic aspects of group choreography. To strengthen the atmosphere in this work, the artist uses live and internal music that is appropriate to the work that the artist is working on. The dancers who support this work consist of six female dancers, of course the selection of dancers by the artist is adjusted to the character, good techniques are also able to apply the ideas and ideas of the work in revealing the problems that the artist wants. This dance work is entitled Nan Tingga, worked on in the form of Traditional dance and has been performed at the Boestanul Arifin Adam Auditorium on January 14, 2026